2020
DOI: 10.3390/nu12123664
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nutrition Education Interventions in Team Sport Players. A Systematic Review

Abstract: Considering nutrition education interventions have been frequently implemented in team sport athletes and have shown promising results, this study aimed to summarize the effects of nutrition education interventions on eating habits, nutrition knowledge, body composition, and physical performance in team sport athletes. A systematic review was conducted using the following databases: PubMed/MEDLINE, Web of Science and SPORTDiscus. A total of 14 studies met the inclusion criteria for the review. The methodologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 52 publications
3
24
1
4
Order By: Relevance
“…The obtained results, indicating incomplete balance of the diet of elite Polish basketball players and significant relationships between the quality of the diet (in the quantitative dimension) and the level of self-efficacy, confirm the legitimacy of further monitoring diet and nutritional education, and taking into account personality traits in activities promoting the proper nutrition of athletes, as indicated by others authors [7, 9,24]. Meta-analytical studies have allowed to confirm that nutritional education of team sports athletes can be an effective strategy for improving their eating habits, nutritional knowledge and body composition [18].…”
Section: Discussionsupporting
confidence: 59%
“…The obtained results, indicating incomplete balance of the diet of elite Polish basketball players and significant relationships between the quality of the diet (in the quantitative dimension) and the level of self-efficacy, confirm the legitimacy of further monitoring diet and nutritional education, and taking into account personality traits in activities promoting the proper nutrition of athletes, as indicated by others authors [7, 9,24]. Meta-analytical studies have allowed to confirm that nutritional education of team sports athletes can be an effective strategy for improving their eating habits, nutritional knowledge and body composition [18].…”
Section: Discussionsupporting
confidence: 59%
“…Till et al [ 37 ] conducted a retrospective study in which it was shown that United Kingdom Academy players with lower skinfolds showed long-term progression in their professional sports careers. As a result, evaluating body fat could be the best way to monitor individual changes in diet and/or personalized training as well as other changes [ 38 , 39 ]. In the rugby union case, anthropometric determinations could also be used as a valuable tool for coaches when assessing the profile or position in the game for each player.…”
Section: Discussionmentioning
confidence: 99%
“…The supposed role of the lower categories in soccer is to act as centers for the selection and development of prospective young soccer players [33]. In this sense, from the lowest category of the club (U8), the club's staff begins to focus on the diet and body composition of its players [34], to attain their best performance. Thus, the main purpose of this investigation was to assess the body composition and adherence to the Mediterranean diet of top-level U12 soccer players.…”
Section: Discussionmentioning
confidence: 99%